The Ethnomathematics in Enhancing Communication Skills among Elementary School Students - Hilliyani, Hilliyani; Saragih, Sahat; Napitupulu, Elvis (International Journal of Trends in Mathematics Education Research, 2024)
Learning mathematics in primary schools often faces challenges in making abstract concepts easier for students to understand. One approach that can address this challenge is ethnomathematics, which integrates elements of local culture into mathematics learning. This research aims to explore how ethnomathematics can be used to improve mathematical communication understanding in primary school students. The research method used is to use a literature review of various sources that examine the importance of training primary school children's communication in mathematics. Ethnomathematics can improve students' understanding of mathematical concepts through a cultural context that is familiar to them. This approach is also effective in training mathematical communication, where students learn to explain their thought processes, discuss with peers, and solve mathematical problems collaboratively. Students who learnt with the ethnomathematics approach showed improved mathematical communication skills, both orally and in writing. The importance of applying ethnomathematics lies in its ability to make mathematics more interesting and meaningful to students, thus increasing their motivation and active participation in learning. In addition, ethnomathematics also encourages the development of critical and creative thinking skills, which are essential in mathematical communication. Although its implementation requires teacher creativity and preparedness, these findings confirm that ethnomathematics is an important and effective approach in mathematics education in primary schools.